Analisis kepekaan hidrograf satuan sintetik gama I dalam penentuan debit banjir rancangan (The Sensitivity Analysis Gama I Synthetic Unit Hydrograph for Design Flood Determination) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The determination of design flood could be conducted with many kind of methods. One of the methods had been developed in Java Island using Gama I synthetic unit hydrograph, however there was a different physical parameter characteristic between the catchment area in Java and that in South Sulawesi. In Jawa Island, the design flood determined by Gama I synthetic unit hydrograph method based on catchment physical parameter in order to obtain the main parameters of unit hydrograph. The Gama I synthetic unit hydrograph method in South Sulawesi could be verified by running examination to this model. The examination was conducted by calculating the deviation between the method of Gama I synthetic unit hydrograph and the observed unit hydrograph. From that the deviation, the coefficient of unit hydrograph equation can be obtained by multiple linear regression. This research had been conducted to six (6) catchment areas in South Sulawesi (i.e., Jenelata, Noling, Kalaena, Maros, Walanae, and Maloso). The results showed that main parameters of unit hydrograph were sensitive to catchment area, source factor, source frequency and main stream length. The Gama I synthetic unit hydrograph method could be applied in South Sulawesi with some adjustment of the catchment physical parameter coefficient which form the unit hydrograph. By that way, an accurate result that close relatively to the actual flood hydrograph could be achieved.